2002
DOI: 10.1002/smr.263
|View full text |Cite
|
Sign up to set email alerts
|

Consistent database sampling as a database prototyping approach

Abstract: Requirements elicitation has been reported to be the stage of software development when errors have the most expensive consequences. Users usually find it difficult to articulate a consistent and complete set of requirements at the beginning of a development project. Prototyping is considered a powerful technique to ease this problem by exposing a partial implementation of the software system to the user, who can then identify required modifications. When prototyping data-intensive applications a so-called pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The closest study we have found associated to our work is the one presented in [4], which focuses on the advantages of constructing prototype databases populated with operational data, and proposes a sampling approach, which selects the data items so that the resulting sample database satisfies some predefined criteria, focusing on the advantage of using prototype databases populated with sampled operational data. Moreover, Olken's major contribution to random sampling from large databases proves sampling to be a powerful technique [11].…”
Section: Related Workmentioning
confidence: 99%
“…The closest study we have found associated to our work is the one presented in [4], which focuses on the advantages of constructing prototype databases populated with operational data, and proposes a sampling approach, which selects the data items so that the resulting sample database satisfies some predefined criteria, focusing on the advantage of using prototype databases populated with sampled operational data. Moreover, Olken's major contribution to random sampling from large databases proves sampling to be a powerful technique [11].…”
Section: Related Workmentioning
confidence: 99%
“…The reader is referred to [7] for a more extended review of existing literature on database prototyping, including an evaluation framework where they can be analysed and compared. Finally, it must be noted that a vast literature exists on database sampling for a large diversity of applications other than database prototyping (eg.…”
Section: Related Workmentioning
confidence: 99%